Foreign Trade as a major aspect of National Security: Does it apply to Nepal? - Sharma, Lila Prasad (Prashasan: The Nepalese Journal of Public Administration, 2024)
National security encompasses safeguarding a state in every aspect-from protecting fundamental values, democratic principles, and societal well-being to ensuring the security of citizens and the integrity of borders. It involves defending territory, maintaining stable economic relationships globally, preserving the functioning of governance institutions, and securing national secrets. National security is intertwined with concepts like national interest, power, and stability. Economic security, which entails having sufficient financial and other resources to live comfortably now and in the future, is a crucial component. It includes job stability, financial sufficiency, and preparedness for unexpected expenses. Without economic security, other forms of security are incomplete. This article explores the empirical concept of national security and its dependency on economic status, with a particular focus on trade.